MEMBANGUN RESILIENSI DALAM DIRI MAHASISWA DI MASA PANDEMI COVID -19 - Emanuel Haru (Jurnal Alternatif Wacana Ilmiah Interkultural, 2022)
The COVID -19 pandemic has had a serious impact on the people of the world, including Indonesians. In Indonesia itself, the COVID -19 pandemic has had a very serious impact on the community in several aspects. They are health, economic, social, educational and religious aspects. One component of society that has felt the impact of the COVID -19 pandemic, is students at a college. In these affected conditions, there are few students experience psychological pressure. Therefore, in dealing with difficult situations, students need to build psychological resilience or what is commonly known as resilience. Resilience is important so that students do not fall into more serious problems as a result of this pandemic. On the other hand, with resilience in them, students persist, adapt and ultimately overcome these difficult situations. Resilience in students at a college can be built by increasing the protective factors in themselves. Protective factors are personal, social, family, and institutional or community safety nets that enable individuals to be able to deal with life's stressors. There are two protective factors that can help increase resilience in students during this pandemic. They are internal protective factors and external protective factors. Internal protective factors are personal safety nets that come from the individual himself in the form of self-esteem, self-efficacy, problem-solving ability, emotion regulation and optimism. This is an internal resource (capacity) that a student can optimize in increasing psychological endurance during this pandemic. While external protective factors are protective factors that come from outside the student, for example support from family and environment.